Challenges in the Implementation of the Community Empowerment Program for Economic Enterprises at the Village Level (P2M-UEK) in the Trade and Plantation Sectors in Pematang Pudu Village, Bengkalis Regency - Wirsa, Jamila Maya; Malau, Hasbullah (The Future of Education Journal, 2025)
This study endeavors to delve into and grasp the challenges encountered in implementing the Village Economic Enterprise Community Empowerment Program (P2M-UEK) within the trade and plantation sectors in Pematang Pudu Village, Bengkalis Regency. Using a descriptive qualitative approach, data were obtained through in-depth interviews and document review. The results indicate that the implementation of the program faces obstacles, including a significant number of loan repayment failures, competition from cooperatives and formal financial institutions, and insufficient outreach or socialization to the public. These challenges negatively affect the smooth circulation of revolving funds and contribute to the community’s limited comprehension and participation in the program. To address these issues, improvements are needed in communication strategies, institutional capacity, and managerial competence to ensure that the goals of community empowerment through the UEK initiative are fully realized.